2006
DOI: 10.1109/lpt.2006.884736
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Broadcast, Transmission, and Wavelength Conversion Functionalities Using Photonic Crystal Fibers

Abstract: Abstract-Broadcasting functionality using cross-phase modulation in a nonlinear optical loop mirror utilizing 100-m highly nonlinear (HNL) photonic crystal fiber (PCF) as nonlinear element is demonstrated. This work presents entirely PCF-based network functionalities including broadcasting, transmission, and wavelength conversion. Broadcasting on four channels, transmission of one selected channel through one partially dispersion compensated 10.4-km PCF transmission link and wavelength conversion using four-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Therefore, PCFs are very suitable for all-optical time demultiplexing [22][23][24], wavelength conversion [7,18], pulse reshaping and other signal processing functions [18,25]. Recently, Zsigri et al successfully demonstrated the functionalities of broadcasting, transmission and wavelength conversion entirely based on PCFs at a bit rate of 10 Gbit s −1 [26], which will be useful for future all-optical networks. Since the reported broadcasting function was implemented by exploiting cross-phase modulation (XPM) in a nonlinear optical loop mirror (NOLM), the resulting configuration can be complex for practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PCFs are very suitable for all-optical time demultiplexing [22][23][24], wavelength conversion [7,18], pulse reshaping and other signal processing functions [18,25]. Recently, Zsigri et al successfully demonstrated the functionalities of broadcasting, transmission and wavelength conversion entirely based on PCFs at a bit rate of 10 Gbit s −1 [26], which will be useful for future all-optical networks. Since the reported broadcasting function was implemented by exploiting cross-phase modulation (XPM) in a nonlinear optical loop mirror (NOLM), the resulting configuration can be complex for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the reported broadcasting function was implemented by exploiting cross-phase modulation (XPM) in a nonlinear optical loop mirror (NOLM), the resulting configuration can be complex for practical applications. Moreover, the OTDM scheme has not yet been considered in the work on using PCFs for wavelength conversion and multicasting as reported in [7,18,19,25,26]. However, future all-optical networks will employ OTDM to efficiently increase the data bit rate per wavelength channel in order to reduce the complexity and power consumption of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Highly nonlinear photonic crystal fibers (PCFs) have been recently employed for optical time demultiplexing up to 160 Gbit s −1 [20][21][22], 40 GS s −1 wavelength-division sampling [23], all-optical modulation-format conversion [24], optical signal regeneration [25], wavelength conversion and multicasting [26][27][28][29][30][31][32]. This is because PCFs possess unique properties which are not provided by conventional optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…This is attractive for all-optical signal processing in future transparent photonic networks. Until now, alloptical wavelength conversion based on FWM in a PCF has been demonstrated at different bit rates [17][18][19][20][21][22]. However, it is noticed that most of the reported works mainly focus on single-to-single channel wavelength conversion, while single-to-multiple wavelength conversion with a multicasting function is highly desirable in practical optical label swapping packet-switched networks.…”
Section: Introductionmentioning
confidence: 99%